СУРХОНДАРЁ ЗОТ ТИПИДАГИ СУР ҚОРАКЎЛ ҚЎЙЛАРИ РАНГБАРАНГЛИГИНИНГ ИРСИЙЛАНИШ СИФАТЛАРИ - Омонов, М.И. (SCIENCE and SOCIETY, 2020)
The article cites materials that show the inheritance and variability of traits of parental pairs that characterize Surkhandarya breed type surakhs when breeding Karakul sheep. It has been established that the main genetic parameter of selection according to colors and the results for homogeneous and heterogeneous selection.